Government Official Political Neutrality in Digital Era: Challenge for Administrative Ethics? - Rino A. Nugroho; Dinda Pramitha Shaila Putri; Teguh Budi Santoso; Daffa Rifqi Utomo; Kristina Setyowati (Iapa Proceedings Conference, 2019)
Political neutrality in bureaucracy is facing new challenges in the digital era. Due to its easiness in expressing someone’s political views, social media has been chosen by people to be actively involved in politics, including government officials. Public administration scholars believe that to maintain its professionalism, government officials should ethically take a clear distance from practical politics. In order to maintain such professionalism in offline world is easier than in online one. Even though online political activity of government official is apparent, very limited studies had conducted in the area. This study aim is to portray the online political activity of government official by using Indonesian 2019 election as the case study. A datamining from social media is used to collecting the data. Content analysis by using both quantitative and qualitative approach is used for analysing the data. Data is first captured using datamining and then quantitatively displayed using descriptive statistics. Qualitative analysis is conducted for gaining the identity of government officials in certain social media accounts. The result indicates that some government officials were unable to maintain its political neutrality. Further discussion on how political neutrality might challenge administrative ethics is discussed in the full paper.